Association between Tobacco Industry Interference Index (TIII) and MPOWER measures and adult daily smoking prevalence rate in 30 countries - Yuri Lee; Siwoo Kim; Min Kyung Kim; Ichiro Kawachi; Juhwan Oh (BMC, 2024)
Abstract Background This study aimed to investigate the impact of tobacco industry interference on the implementation and management of tobacco control and the tobacco epidemic using the Tobacco Industry Interference Index (TIII) and MPOWER-a package of measures for tobacco control-and adult daily smoking prevalence in 30 countries. Methods The TIII was extracted from the Global Tobacco Industry Interference Index 2019 and Global Center for Good Governance in Tobacco Control (GGTC). MPOWER measures and adult daily smoking prevalence rate were extracted from the World Health Organization (WHO) report on the global tobacco epidemic in 2021. We assessed the ecological cross-lagged association between TIII and MPOWER scores and between TIII and age-standardized prevalence rates for adult daily tobacco users. Results Tobacco industry interference was inversely correlated with a country's package of tobacco control measures (β = -0.088, P = 0.035). The TIII was correlated with weaker warnings about the dangers of tobacco (β = -0.016, P = 0.078) and lack of enforcement of bans on tobacco advertising promotion and sponsorship (β = -0.023, P = 0.026). In turn, the higher the TIII, the higher the age-standardized prevalence of adult daily tobacco smokers for both sexes (β = 0.170, P = 0.036). Adult daily smoking prevalence in males (β = 0.417, P = 0.004) was higher in countries where the tobacco industry received incentives that benefited its business. Conclusion Where the interference of the tobacco industries was high, national compliance with the Framework Convention on Tobacco Control (FCTC) was lower, and the prevalence of adult daily smokers higher. National governments and global society must work together to minimize the tobacco industry's efforts to interfere with tobacco control policies.